Monitoring treatment response in psoriasis: current perspectives on the clinical utility of reflectance confocal microscopy - Agozzino M; Noal C; Lacarrubba F; Ardigò M (Dove Medical Press, 2017)
Marina Agozzino,1 Cecilia Noal,2 Francesco Lacarrubba,3 Marco Ardigò4 1Dermatology Unit, Second University of Naples, Naples, 2Dermatology Unit, University of Trieste, Trieste, 3Dermatology Clinic, University of Catania, Catania, 4Clinical Dermatology Department, San Gallicano Dermatological Institute, Istituto di Ricovero e Cura a Carattere Scientifico, Rome, Italy Abstract: Reflectance confocal microscopy (RCM) evaluation of inflammatory skin diseases represents a relatively new technique that, during the past 5 years, has attracted increasing interest, with consequent progressive increment of publications in literature. The success of RCM is directly related to the high need for noninvasive techniques able to both reduce the number of skin biopsies and support clinical diagnosis and patient management. RCM helps to visualize microscopic descriptors of plaque psoriasis (PP) with good reproducibility between observers and a high grade of correspondence with histopathology. Several clinical tests are used for the therapeutic management of PP, but they are limited by subjective interpretation. Skin biopsy presents objective interpretation, but the procedure is invasive and not repeatable. RCM has been used not only for the evaluation of skin cancer or inflammatory skin diseases, but also for monitoring the efficacy of different treatments in PP. In this review, we present some examples of RCM applications in therapeutic psoriasis follow-up. Keywords: reflectance confocal microscopy, psoriasis noninvasive follow-up, psoriasis monitoring